The effect of using the assistive devices on quality of life in mothers of children with cerebral palsy - Bemanali Mardani Shahrbabak; Nasrin Jalili; Seyed Majid Mirkhani; Pouria Reza Soltani (Vesnu Publications, 2013)
Introduction: Functional impairments can reduce the child's participation in daily routine activities for children with cerebral palsy and lead to physical and psychological stress on caregivers. This disability can, in turn, have a negative effect on quality of life of mothers. The purpose of this study was to explore the effects of assistive device on quality of life in mothers of children with cerebral palsy (CP). Materials and Methods: In this quasi experimental study, two hundreds and ninety one mothers of cerebral palsy children aged 0 to 14 residing in Tehran in 2011 were selected by convenience sampling method. Considering to the levels of gross motor function and manual ability of children with CP, assistive devices were provided for them. Then SF-36 Questionnaire was used to assess the mother`s quality of life. The severity of cerebral palsy and manual ability were assessed using the Gross Motor Function Classification system and manual ability classification system respectively. Descriptive statistics and Paired -T test were used for analyzing the data. Results: The mothers' mean age was 36.69 years (SD = 6.15). The results indicated that subjects demonstrated a significant increase from pretests to posttests in role limitations due to physical health (P = 0.001), Pain (P = 0.004), emotional well being (P < 0.001), vitality (P < 0.001) As well as the overall dimensions of mental health (P = 0.008), physical health (P = 0.006) and total quality of life (P = 0.001). However, there was no significantly difference between pre-test and post-test of other subscales (P > 0.05). Conclusion: According to the results, assistive devices can provide help and improve the quality of life of mothers with cerebral palsy children. It also would be considered as a support for these children and their families. Keywords: Assistive device, Cerebral palsy, Quality of life of mothers